Exploring the Mystique of Seven: An Interdisciplinary Analysis of Its Significance in Astronomy, Culture, and Human Life - Belay Sitotaw Goshu; Muhammad Ridwan (Lakhomi Journal Scientific Journal of Culture, 2024)
Seven is significant in many spheres of human cognition, culture, and science; it captivates the imagination and has deep symbolic meaning in many cultures and historical periods. This study traced the significance of the number seven in religious traditions, cultural behaviors, and scientific occurrences to examine the multidimensional nature of this number. Seven is a hallowed number in religious contexts, signifying spiritual fulfillment, divine wholeness, and perfection. The number seven is found in many religious stories and rites, representing cosmic harmony and divine order. It includes the seven days of creation in Judeo-Christian texts and the seven heavens in Islamic cosmology. It indicates cyclicality, renewal, and transition and can be found in mythology, folklore, and other cultural expressions. The number seven enhances human expression and creativity in literature, music, and the art of narrative structure, artistic composition, and aesthetic beauty. Seven appears throughout astronomical events, mathematical formulas, and natural cycles, exposing patterns and structures that control the universe through scientific investigation. The number seven highlights the mathematical beauty and complexity of the natural world. It includes the seven hues of the rainbow and the seven musical notes in the diatonic scale. This study emphasized how numerical symbolism in human culture and civilization continues to be fascinating and resonate by examining the significance of seven throughout religious, cultural, and scientific areas. Our understanding of numbers that affect our perceptions, beliefs, and experiences is deepened via interdisciplinary research and discussion, which inspires us to consider the mysteries of existence and the interconnectedness of all things.